Occurrence of protozoans & their limnological relationships in some ponds of Mathbaria, Bangladesh - Mozumder, Pronob Kumar; Banu, Marjia Akhter; Naser, M Njamul; Ali, Md Shahadat; Alam, Munirul; Sack, R Bradley; Colwell, Rita R; Huq, Anwar (University Journal of Zoology, Rajshahi University, 2012)
DOI: http://dx.doi.org/10.3329/ujzru.v29i1.9470 UJZRU 2010; 29(1): 69-71